2015
DOI: 10.1007/s00213-015-3927-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparing treatment effects of oral THC on simulated and on-the-road driving performance: testing the validity of driving simulator drug research

Abstract: RationaleThe driving simulator provides a safe and controlled environment for testing driving behaviour efficiently. The question is whether it is sensitive to detect drug-induced effects.ObjectiveThe primary aim of the current study was to investigate the sensitivity of the driving simulator for detecting drug effects. As a case in point, we investigated the dose-related effects of oral ∆9-tetrahydrocannabinol (THC), i.e. dronabinol, on simulator and on-the-road driving performance in equally demanding drivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 30 publications
3
39
1
Order By: Relevance
“…Results show that driving stability is impaired after THC intake, both in simulated and real driving conditions. Globally, these results are coherent with the results of previous studies involving simulation or real driving conditions . In Lenné et al.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results show that driving stability is impaired after THC intake, both in simulated and real driving conditions. Globally, these results are coherent with the results of previous studies involving simulation or real driving conditions . In Lenné et al.…”
Section: Discussionsupporting
confidence: 90%
“…We selected ILC as our main outcome criterion to quantify driving impairment after THC intake, as several studies showed that accidents related to a diminution of awareness frequently occur after an ILC with a single car driving off the road without reaction from the driver . Other studies evaluating the effects sleepiness, alcohol or benzodiazepine intake on driving performance in simulated and real conditions reported similar results . For example, Philip et al.…”
Section: Discussionmentioning
confidence: 99%
“…The lane-keeping performance obtained in this study is slightly better than found in real cars, with a standard deviation of lateral position [SDLP] of about 0.10 m, whereas values of 0.15-0.20 m are typically observed in on-road experiments (see Veldstra et al, 2015;Verster and Roth, 2011). This difference may be caused by the narrow road and real-time feedback on performance.…”
Section: Driving Simulator Versus On-road Testscontrasting
confidence: 51%
“…This may also be reflected in reduced motivation to perform the test. Driving simulators also showed to be less sensitive in detecting relative modest drug effects when directly compared to on-road driving [13]. Further, sleepiness scores are usually higher in simulator settings when compared to on-road driving tests [14].…”
Section: Discussionmentioning
confidence: 99%